Spinal Arachnoiditis in Patients with Coccidioidomycosis Meningitis—Analysis of Clinical and Imaging Features - Sivasubramanian, Geetha; Kadakia, Saurin; Kim, Jani M.; Pervaiz, Sarah; Yan, Yueqi; Libke, Robert (Journal of fungi (Basel), 2022)
Background: Coccidioidomycosis meningitis (CM) is the most aggressive form of coccidioidomycosis, requiring lifelong antifungal treatment and often cerebrospinal fluid (CSF) diversion. Long-standing CM can be associated with spinal complications such as arachnoiditis. However, studies describing the frequency, clinical, and imaging characteristics of arachnoiditis in patients with CM are limited. Methods: We identified 133 patients with CM based on CSF culture, PCR, or serology between January 2010 and December 2020. Of these, 37 patients underwent spinal imaging. Data on demographics, risk factors, symptoms, antifungal therapy, surgical management, follow-up visits, adherence, serological trends, and imaging findings were reviewed. Results: Abnormal findings were observed in 30 of the 37 patients with CM who underwent spinal imaging. The imaging abnormalities noted in our study included leptomeningeal enhancement (53%), arachnoiditis (53%), syringomyelia (23%), cord signal abnormalities (10%), and osteomyelitis (7%). Of the 30 patients, 90% had symptoms, such as weakness, numbness, or urinary retention. The incidence of arachnoiditis in the present study was 12%. Higher initial CSF protein levels and intra cranial pressure were associated with a higher risk of developing arachnoiditis/syringomyelia. Management of CM was challenging, as evidenced by shunt failure (46%), medication non-compliance (57%), and lack of adequate follow-up (60%). Persistent disabilities were noted in 62% of the patients. Conclusions: Patients with CM develop spinal complications such as arachnoiditis, or syringomyelia. Many cases may go undetected due to lack of symptoms in early stages. CM management challenges such as shunt failure, lack of follow-up care, and medication noncompliance, were frequent.